Quantum dot bio-conjugate: as a western blot probe for highly sensitive detection of cellular proteins - Kale, Sonia; Kale, Anup; Gholap, Haribhau; Rana, Abhimanyu; Desai, Rama; Banpurkar, Arun G.; Ogale, Satishchandra; Shastry, Padma (Journal of Nanoparticle Research, 2012)
In the present study, we report a quantum dot (QD)-tailored western blot analysis for a sensitive, rapid and flexible detection of the nuclear and cytoplasmic proteins. Highly luminescent CdTe and (CdTe) ZnS QDs are synthesized by aqueous method. High resolution transmission electron microscopy, Raman spectroscopy, fourier transform infrared spectroscopy, fluorescence spectroscopy and X-ray diffraction are used to characterize the properties of the quantum dots. The QDs are functionalized with antibodies of prostate apoptosis response-4 (Par-4), poly(ADP-ribose) polymerases and beta actin to specifically bind with the proteins localized in the nucleus and cytoplasm of the cells, respectively. The QD-conjugated antibodies are used to overcome the limitations of conventional western blot technique. The sensitivity and rapidity of protein detection in QD-based approach is very high, with detection limits up to 10 pg of protein. In addition, these labels provide the capability of enhanced identification and localization of marker proteins in intact cells by confocal laser scanning microscopy.
Keywords: Detection; Imaging; nanomedicine; quantum dot; Rapid; sensors; Western blot